Pengaruh Kapasitas Individu, Skema Pemberian Intensif pada Budgetary Slack dengan Technological Skills sebagai Variable Moderasi - Azizah, Anisah Nurul; Muslimin, Muslimin (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to examine the effect of Individual Capacity, and intensive granting schemes on Budget Bargaining with technological skill as moderation. The population in this study were employees of PERUMDA Panglungan Jombang Regency. Sample withdrawal using purposive sampling technique. This research uses a quantitative approach with Statistical Program for Social Science (SPSS) 26 analysis techniques. The sample of this study was 74 respondents consisting of permanent employees and daily employees involved in the budget process. This study uses multiple linear regression analysis. Based on the results obtained from this study, it shows that individual capacity has an effect on budget constraints, intensive provision schemes also have a significant effect on budget constraints, so it can be concluded that the variables of Individual Capacity and Intensive Provision Schemes affect Budget Concealment. With the existence of tecnologicall skill as a moderating variable, it has an effect on individual capacity and intensive giving schemes on budget constraints. The technological skills possessed by employees can reduce the budget gap that occurs due to an increase in the individual capacity of employees. Keywords: Budgetary Slack, Individual Capacity, intensive granting schemes, tecnologicall skill